Pengembangan Perangkat Pembelajaran Materi Chasis Untuk Mendukung Implementasi Kurikulum Merdeka di SMK - Suhartanta, Suhartanta; Wakid, Muhkamad; Efendi, Yosep (Universitas Negeri Yogyakarta, 2024)
Abstract This research aims to develop chassis material learning tools that are able to train vehicle chassis system inspection, repair and maintenance skills for vocational school students in the Automotive Engineering Skills Program to support the implementation of the Merdeka Curriculum. This R&D research was carried out at SMKN 2 Pengasih, namely on Class XI students of the Automotive Engineering Skills Program. The stages of developing learning tools consist of four phases, namely define, design, develop, and disseminate. The define stage includes literature study activities and field surveys for the purposes of problem identification and needs analysis; the design stage includes initial product design activities; the develop stage includes expert validation activities and product revision; while the disseminate stage includes product implementation activities in the field. Data collection techniques used include observation, documentation and questionnaire techniques. Data analysis uses quantitative and qualitative descriptive analysis techniques. The results of research and development show that the teaching modules, learning materials, LKPD, learning media and assessment instruments that have been developed are included in the very feasible category. The test results for all the independent curriculum learning tools obtained results of 93% (very good). Thus, the learning tools that have been developed are suitable for use in order to support the implementation of the Merdeka Curriculum in Vocational Schools. Key Words: Teaching Module; Vehicle Chassis; Merdeka Curriculum in Vocational Schools